Application of Oxide Coatings for Improved Steel Filtration with the Aid of a Metal Casting Simulator1. Issue 12 (9th September 2013) - Dudczig, Steffen; Aneziris, Christos G.; Dopita, Milan; Rafaja, David; Aneziris, Christos G.
<x xml:space="preserve">Abstract</x> Slip casted, carbon bonded nozzles with active mullite coating arehave been simultaneously tested with uncoated nozzles in a steel casting simulator according to their clogging behavior against endogenous as well as exogenous non‐metallic inclusions. After the tests with inclusions containing steel melt no clogging of particles could be observed on the active mullite coating after steel melt contact. The investigations show a position‐dependent partially till completely decomposition of the mullite coating into coarse grained alumina‐rich particles and a second phase with a main composition in the ternary system MnO–SiO2–Al2O3. It has been verified that these decomposition was caused by multiple reactions between the mullite coating and the substrate during heat‐up as well as interactions between the coating and alloying elements of the steel melt during the tests.